2010
DOI: 10.1001/archgenpsychiatry.2010.38
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Familial Transmission of Schizophrenia Psychosis Spectrum and Affective Psychoses in the New England Family Study’s High-Risk Design

Abstract: Context There is a long history of research on the familial transmission of schizophrenia and other psychoses. However, few studies have investigated the specificity of the transmission of schizophrenia-psychosis spectrum (SPS) disorders and affective psychoses (APs) or observed high-risk offspring into mid-adulthood. Objectives To investigate the transmission of psychoses from parents to their offspring and the specificity of transmission across psychosis subtypes. Design High-risk follow-up study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 77 publications
6
61
2
4
Order By: Relevance
“…Inconsistent results have been reported regarding the question whether the predictive value of parental psychopathology for psychopathology in the offspring is disorder specific (Goldstein, Buka, Seidman, & Tsuang, 2010;van Meurs et al, 2009), (internalising/externalising) spectrum specific (Kessler, Davis, & Kendler, 1997) or more diffuse (Bijl, Cuijpers, & Smit, 2002;Keshavan et al, 2008). The present results suggest that general parental psychopathology is associated with a broader spectrum of mild psychotic symptomatology, as represented by the measurement of (cross sectional) experiences at age 15 16 years, capturing both potentially transitory and persistent phenomena.…”
Section: Discussioncontrasting
confidence: 41%
“…Inconsistent results have been reported regarding the question whether the predictive value of parental psychopathology for psychopathology in the offspring is disorder specific (Goldstein, Buka, Seidman, & Tsuang, 2010;van Meurs et al, 2009), (internalising/externalising) spectrum specific (Kessler, Davis, & Kendler, 1997) or more diffuse (Bijl, Cuijpers, & Smit, 2002;Keshavan et al, 2008). The present results suggest that general parental psychopathology is associated with a broader spectrum of mild psychotic symptomatology, as represented by the measurement of (cross sectional) experiences at age 15 16 years, capturing both potentially transitory and persistent phenomena.…”
Section: Discussioncontrasting
confidence: 41%
“…This result would suggest a certain heritability of ''psychotic'' clinical dimension and adds a new element in the actual debate about the opportunity to consider PMD as a diagnosis per se. In support of this hypothesis a recent study found that the offspring of schizophrenic patients had a doubling risk for ''Affective Psychosis'' respect to controls (Goldstein et al, 2010). In addition a genetic study found that the allele A of the gene of dopamine bhydroxylase was associated with delusional ideation in a sample of major depressives, confirming the genetic predisposition to develop psychotic symptoms (Wood et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…We would speculate that this risk is increased as high risk individuals who later convert to psychosis have more severe neuropsychological impairment than non-converters and converters with a positive family history of psychosis have the most severe neuropsychological impairment prior to onset of psychosis . Other publications with this NEFS high-risk project have reported on rates of psychotic disorders in adulthood [Goldstein et al, 2010[Goldstein et al, , 2011. Consistent with previous high-risk samples, approximately 12% of the high-risk offspring met lifetime Family SES: socioeconomic-index, measured as a composite index of family income, education, and occupation according to the system used by the United States Bureau of the Census, ranging from 0.0 ("lowest") to 9.5 ("highest").…”
Section: Discussionmentioning
confidence: 99%